Emulation of free space optical link in weak atmospheric turbulence. Issue 5 (8th April 2018) - Anandkumar, D.; Sangeetha, R. G.
Abstract: In this paper, the performance of FSO communication link under weak atmospheric turbulence has been analyzed in terms of received power, Bit Error Rate for various data rates. The results have been simulated using R‐soft OptSim 2015a environment and validated using hardware test bed setup.